Effect of composition on electrical properties of lead-free Bi 0.5(Na0.80K0.20)0.5TiO 3-(Ba0.98Nd0.02)TiO3 piezoelectric ceramics - Jaita P. (2014)
Lead-free piezoelectric ceramics with the composition of (1-x)Bi 0.5(Na0.80K0.20)0.5TiO 3-x(Ba0.98Nd0.02)TiO3 or (1-x) BNKT-xBNdT (with x = 0-0.20 mol fraction) have been synthesized by a conventional mixed-oxide method. The compositional dependence of phase structure and electrical properties of the ceramics were systemically studied. The optimum sintering temperature of all BNKT-BNdT ceramics was found to be 1125°C. X-ray diffraction pattern suggested that BNdT effectively diffused into BNKT lattice during sintering to form a solid solution with a perovskite structure. Scanning electron micrographs showed a slight reduction of grain size when BNdT was added. It was found that BNKT-0.10BNdT ceramic exhibited optimum electrical properties (εr = 1716, tanδ = 0.0701, T c = 327°C, and d33 = 211 pC/N), suggesting that this composition has a potential to be one of a promising lead-free piezoelectric candidate for dielectric and piezoelectric applications. © 2013 AIP Publishing LLC.